Relationship Between Measures of Adiposity, Arterial Inflammation, and Subsequent Cardiovascular Events - Figueroa, Amparo L. (Circ Cardiovasc Imaging, 2016)
BACKGROUND: The objective of this study was to evaluate how different measures of adiposity are related to both arterial inflammation and the risk of subsequent cardiovascular events. METHODS AND RESULTS: We included individuals who underwent FDG PET/CT imaging for oncological evaluation. Subcutaneous adipose tissue (SAT) volume, visceral adipose tissue (VAT) volume and VAT/SAT ratio were determined. Additionally BMI, metabolic syndrome (MetS), and, aortic FDG uptake (a measure of arterial inflammation) were determined. Subsequent development of cardiovascular disease (CVD) events was adjudicated. The analysis included 415 patients with a median age of 55 (P25–P75: 45–65) and a median BMI of 26.4 (P25– P75: 23.4–30.9) kg/m(2). VAT and SAT volume were significantly higher in obese individuals. VAT volume (r=0.290, p<0.001) and VAT/SAT ratio (r=0.208, p<0.001) were positively correlated with arterial inflammation. 32 subjects experienced CVD event during a median follow-up of 4 years. Cox proportional hazard models showed that VAT volume, and VAT/SAT ratio were associated with CVD events (hazard ratio, HR (95% CI): 1.15 (1.06–1.25, p<0.001; 3.60 (1.88–6.92), p<0.001 respectively). BMI, MetS and SAT were not predictive of CVD events. CONCLUSIONS: Measures of visceral fat are positively related to arterial inflammation and are independent predictors of subsequent CVD events. Individuals with higher measures of visceral fat as well as elevated arterial inflammation are at highest risk for subsequent CVD events. The findings suggest that arterial inflammation may explain some of the CVD risk associated with adiposity.